Pengaruh Kedisiplinan Terhadap Kinerja Pegawai Pada PT. Bank Artha Graha Internasional, TBK. - Muhammad Rhama Rodiyansyah (Science of Management and Students Research Journal (SMS), 2019)
This study entitled The Effect of Discipline on Performance at PT. Bank Artha Graha Jambi Branch, Research focuses on finding whether the influence of discipline on employee performance and how much influence is obtained. This research is a quantitative descriptive study, using simple linear regression analysis and t test, it is known that discipline has a positive effect on employee performance at PT. Bank Artha Graha Jambi Branch. From the regression coefficient analysis the magnitude of the effect is 65.1% while the remaining 34.9% is influenced by other variables outside this study.